ANALISIS FAKTOR YANG MEMPENGARUHI KETEPATAN KELULUSAN MAHASISWA DENGAN ALGORITMA REGRESI LINEAR - Putri, Rani Kurnia; Athoillah, Muhammad; Haqiqiyah, Arina (LPPM Universitas Bina Bangsa, 2024)
Student graduation is an important achievement in higher education which reflects success in completing studies by fulfilling the requirements set by the university. Graduation accuracy, which refers to the extent to which students complete their study program according to the set target time, also has a crucial role in the world of education. In this context, analysis of the factors that influence the accuracy of student graduation becomes important. In this research, analysis was carried out using a linear regression algorithm to understand the factors that influence student graduation at PGRI Adi Buana University Surabaya. The results of the analysis show that the Cumulative Achievement Index (GPA), Class Type, and Program Studi (Prodi) variables have a significant influence on the accuracy of student graduation. The best regression model selected has a high level of accuracy, indicating its effectiveness in explaining the data. The conclusions from this analysis provide in-depth insight into the factors that influence student graduation as well as the suitability of the model in explaining this phenomenon